Persepsi Nelayan Terhadap Ice Flake Machine Sebagai Sarana Rantai Dingin di Kota Padang - Fitria Wahyu Andriani; Yusra Yusra; Guntur Adhi Rahmawan (Jurnal Airaha, 2021)
This study aimed to determine fishers' perceptions of IFM as a cold chain tool in Padang City. The data used in this study were from interviews/questionnaires with IFM managers and anglers around the City of Padang. We also employed fish caught data in 2019 and ice flake sales from 2 (two) IFM providers in Padang City from January to August 2019. The statistical analysis used was linear regression. Most anglers did not know the IFM machine's availability and how to treat the fishery products using ice (cold chain systems). The lack of socialization from the provider to fishers and fisheries business parties in the surrounding area is believed to cause the decreased demand for ice flakes, resulting in the inactive operation of IFM’s in Padang City.